A Novel Organic Solvent Tolerant NAD+-dependent Formate Dehydrogenase from Halophilic Yeast Candida diddensiae - Kurt-Gur, G.; Arslan, E.; Bassarac, Oe.; Ordu, E. (PLEIADES PUBLISHING INC, 2024)
Characterization of new halophilic enzymes capable of thriving in non-aqueous biocatalysis of significant interest in the non-aqueous chemoenzymatic processes. Despite the number of studies dealing with increasing the stability of NAD(+)-dependent formate dehydrogenases (FDHs), there are few studies characterizing their behavior in organic solvents. FDHs have a great advantage in cofactor regeneration systems and the reduction of CO2 to formate. It is important to find novel FDHs for the wide application field of organic chemicals. In this study, a novel NAD(+)-dependent formate dehydrogenase from Candida diddensiae YLP9 (CdFDH), isolated from olive brine and having tolerance under low pH and high salt concentration, was heterologously expressed and characterized. Recombinant CdFDH has optimum activity at pH 7.0-8.0 when the substrate is formate. The midpoint of thermal inactivation (T-0.5) for CdFDH was calculated as 54 degrees C. The enzyme shows high stability at & rcy;& Ncy; 6.0 and 53 degrees & Scy; (k(in )(ef)( 0.28 x 10(-4) /s). Comparing the enzyme activity results obtained from incubation of enzyme in media without salt and with different concentrations of NaCl, KCl, and MgCl2 revealed that concentrations of NaCl and KCl between 0.4-4.0 M contribute to proper folding and activity of CdFDH. Enzyme activity was preserved and significantly increased after incubating in the 20-80% of DMSO, 40% 3-methyl butanol, 70% n-butanol and, all tested concentrations of n-hexane. The results show that NAD+-dependent CdFDH is a promising candidate biocatalyst to use in non- or low-aqueous biotechnological applications.
Keywords: thermal stability; organic solvent stability; non-aqueous biosynthesis; recombinant formate dehydrogenase; Candida diddensiae; ENZYMES; PURIFICATION; STABILITY; SALT; Biotechnology & Applied Microbiology; Microbiology